Literature Review: Effect of Water-Based Exercise on Chronic Obstructive Pulmonary Disease (COPD) Patients - Iwandani, Nuzhulul Lifqi; Rosyid, Fahrun Nur (INDOGENIUS, 2025)
Background & Objective: Chronic Obstructive Pulmonary Disease is a chronic condition of injury to the respiratory tract due to exposure to toxic gases or substances. The various clinical manifestations caused have a major effect on the patient's quality of life. Water-based exercise is a non-pharmacological intervention that helps improve the functional of the lung organs so that the quality of life increases. The purpose of this study was to determine the effect of water-based exercise for COPD patients. Method: This type of research uses the literature review method through google, google schoolar, ncbi, openknowledge and garuda in the range of published years 2018 to 2023 using the keywords water-based exercise; water exercise; water-based exercise; COPD; COPD; Chronic Obstructive Pulmonary Disease; Chronic Obstructive Pulmonary Disease. Result: From the five journals analyzed, participants experienced functional improvements in lung function, respiratory muscle strength, and tolerance to physical activity or exercise. Conclusion: Water-based exercise provides several benefits for people with COPD, including improving lung function, increasing respiratory muscle strength, and optimizing tolerance to physical activity so that quality of life can be supported slowly.